Nigeria Social Studies Teachers’ Perceived Competence and Impact of Environmental Education - Ogunyemi, Biodun; Ifegbesan, Ayodeji P.; Lawal, Moshood B. (NIU Journal of Educational Research, 2024)
This study investigated teachers’ areas of competence and perceived impact of Environmental Education (EE) in Nigeria. A structured questionnaire was administered on four hundred and eleven (411) teachers from thirty selected secondary schools’ teachers selected across five local government areas in Ogun State, Nigeria were administered with a structured questionnaire. The results showed that teachers were not competent in the five areas of competency examined and were not well prepared for teaching Environmental Education (EE) during their training. Furthermore, majority of teachers believed that EE would impact positively on the students. Nevertheless, teachers’ competence and perceived impact of EE did not significantly differ based on gender or the class taught. However, teachers of senior and junior classes had very different perceptions of the impact of EE. ANOVA test showed that significant difference was found in teachers’ area of competence and perceived impact of EE based on their school location, and education qualifications. The results also revealed weak relationship between area of competence and perceived impact of EE. Keywords:   Social studies, Competence, impact, environmental education, Nigeria